Strategi Diferensiasi Dalam Perencanaan Pembelajaran Untuk Mengakomodasi Beragam Gaya Belajar - Yuyun Efrianefrian (Jurnal Sultra Elementary School, 2024)
In the context of modern education, recognition of the diversity of students' learning styles is an important element in effective learning planning. Differentiation strategies offer an adaptive approach to meet individual learning needs by providing flexibility in methods, content, and assessment. This article aims to explore the concept, implementation, and challenges of differentiation strategies in learning, with a focus on how these strategies can improve student learning outcomes. Using a literature study method, this article presents the latest findings that are relevant to be applied at various levels of education.